Low-resistance Ohmic contact on polarization-doped AIGaN/GaN heterojunction - 李世彬 余宏萍 张婷 陈志 吴志明 (中国物理B：英文版, 2014)
High electronic density is achieved by polarization doping without an impurity dopant in graded AIGaN films. Low specific contact resistance is studied on the polarization-doped A1GaN/GaN heterojunctions by using the transmission line method （TLM）. The sheet density of polarization-doped A1GaN/GaN heterojunction is 6 × 10 14 cm-2 at room temperature. The linearly graded material structure is demonstrated by X-ray diffraction. The cartier concentration and mobility are characterized by a temperature-dependent Hall measurement. Multiple-layer metal （Ti/A1/Ti/Au） is deposited and annealed at 650 ℃ to realize the Ohmic contacts on the graded A1GaN/GaN heterojunctions.